2018
DOI: 10.1002/ajmg.c.31612
|View full text |Cite
|
Sign up to set email alerts
|

Functions of TGIF homeodomain proteins and their roles in normal brain development and holoprosencephaly

Abstract: Holoprosencephaly (HPE) is a frequent human forebrain developmental disorder with both genetic and environmental causes. Multiple loci have been associated with HPE in humans, and potential causative genes at 14 of these loci have been identified. Although TGIF1 (originally TGIF, for Thymine Guanine-Interacting Factor) is among the most frequently screened genes in HPE patients, an understanding of how mutations in this gene contribute to the pathogenesis of HPE has remained elusive. However, mouse models base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 92 publications
0
12
0
Order By: Relevance
“…Tgifs are well characterized as repressors of TGFβ-responsive transcription (Wotton et al 1999a;Wotton and Taniguchi 2018) and have been suggested to promote Wnt-responsive gene expression (Zhang et al 2015;Wang et al 2017). We therefore examined expression of genes that are known targets of these pathways.…”
Section: Transcriptional Changes In Tgif Mutant Tumorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tgifs are well characterized as repressors of TGFβ-responsive transcription (Wotton et al 1999a;Wotton and Taniguchi 2018) and have been suggested to promote Wnt-responsive gene expression (Zhang et al 2015;Wang et al 2017). We therefore examined expression of genes that are known targets of these pathways.…”
Section: Transcriptional Changes In Tgif Mutant Tumorsmentioning
confidence: 99%
“…In addition to SMAD interaction, other mechanisms for TGFβ pathway inhibition have been suggested, including promoting SMAD2 ubiquitylation and degradation or preventing SMAD2 phosphorylation in response to TGFβ signaling (Seo et al 2004(Seo et al , 2006. Loss-of-function TGIF1 mutations are associated with holoprosencephaly (HPE), a severe genetic disease affecting forebrain development (Wotton and Taniguchi 2018). Mouse models of Tgif1 and Tgif2 loss of function suggest they play a redundant, but essential role in early embryogenesis (Powers et al 2010).…”
mentioning
confidence: 99%
“…The PACAP gene is expressed in lateral ventricles, dentate line and hypothalamus producing the proliferation of nervous system cells, and has been associated with changes in sensitivity, learning and olfactory aspects 13 . The TGIF gene is related to the development of brain disease and has been observed to be expressed in the cortex of mice 14 . The DLGAP gene is expressed in synaptic sites of hippocampal dendritic spine and cerebral cortex of mice 15 .…”
Section: Discussionmentioning
confidence: 99%
“…We focused on TFs found in each cluster as they may play a role in the regulation of NPC differentiation in both species. TFs found in the early group include important ESC maintenance genes like NANOG (JNR14), POU5F1 (JNR10), and NRSF/REST (JNR14), and important early neuronal differentiation genes, ZIC3 (JNR1), TGIF1 (JNR10), and GBX2 (JNR14) (Martinez- Barbera et al 2001;David Wotton 2018). TFs found in the later expression clusters like, JUND (JNR5), SOX11 (JNR5), MEIS3 (JNR8), JUN (JNR8), JUNB (JNR8), ID1 (JNR8), RARG (JNR3), RARA (JNR5), TEAD2 (JNR3), PBX1 (JNR3), and SALL2 (JNR3), are more likely to be involved in the final stages of NPC differentiation or NPC maintenance (Golonzhka et al 2015).…”
Section: Distinct Transcriptional and Chromatin Accessibility Trajectmentioning
confidence: 99%